2008
DOI: 10.1007/s10802-008-9240-x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Life Events and Chronic Adversities as Antecedents to Anxiety in Children: A Matched Control Study

Abstract: The present study compared the number of severe life events and chronic adversities as reported retrospectively by mothers of children with an anxiety disorder (n=39) prior to the onset of their most recent episode, with controls (n=39) matched for age and sex. The parent version of the Psychosocial Assessment of Childhood Experiences (PACE) was used to assess chronic adversities (long-term experiences with negative impact on child) and severe life events (discrete life events with high long-term threat). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 37 publications
(61 reference statements)
7
46
2
1
Order By: Relevance
“…Congruent to earlier findings [1,19] the results of the present study showed that anxiety-disordered children experience significantly more negative life events compared to their non-anxious counterparts. Adjusted for the 'lifetime' experience of negative life events, anxiety-disordered, and non-anxious children differed in their use of cognitive coping strategies.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Congruent to earlier findings [1,19] the results of the present study showed that anxiety-disordered children experience significantly more negative life events compared to their non-anxious counterparts. Adjusted for the 'lifetime' experience of negative life events, anxiety-disordered, and non-anxious children differed in their use of cognitive coping strategies.…”
Section: Discussioncontrasting
confidence: 84%
“…Cognitive coping is considered to act as a mediator and moderator of the association between stress and psychological well being [6,7]. Cognitive coping might be particularly important to examine in relation to childhood anxiety disorders, as anxiety-disordered children experience significantly more stressful situations (i.e., negative life events) than their non-anxious counterparts and perceive these situations as more threatening [1,13,19]. Maladaptive or excessive use of cognitive coping strategies might contribute to the development and persistence of anxiety disorders in children.…”
Section: Introductionmentioning
confidence: 99%
“…Ratings of contextual (panel) and subjective (parent-rated) impact are assigned using a 4-point scale (0-3), with higher scores indicating greater negative or positive impact. Short-term impact ratings were not examined as it is chiefly life events with long-term negative impact (threat) that are associated with psychopathology (Allen et al 2008;Sandberg et al 1993Sandberg et al , 2001. In the current sample, intraclass correlation coefficients (ICCs) revealed substantial agreement for panel assessment and maternal PACE report on the frequency of negative and positive life events (.87, .94).…”
Section: Methodsmentioning
confidence: 90%
“…While anxiety is generally a prime candidate for prevention, children facing high socioeconomic adversity are acutely at-risk (Allen et al 2008;Duncan et al 1994). In addition to a lack of security and predictability in their day to day lives, children living in poverty are more likely to be exposed to trauma, violence or family conflict, conferring further risk for emotional disorders (Margolin and Gordis 2000;McDonald et al 2007).…”
Section: Introductionmentioning
confidence: 99%